Unemployment and Its Impact on Economic Development (The Case of Georgia) - Zhorzholiani, Tinatin (European Scientific Journal, ESJ, 2023)
This study explores the intricate relationship between unemployment and economic development, with a specific focus on the case of Georgia. High unemployment rates often signal economic challenges within a nation, and their consequences can extend far beyond the labor market. By examining Georgia’s experience, this research aims to shed light on the multifaceted nálisis unemployment on various facets of economic growth. Drawing from statistical data and regression nálisis, this study investigates the causal links between unemployment levels and key economic indicators. It delves into how unemployment rates influence factors such as GDP growth, income inequality, social welfare programs, and overall societal well-being. Furthermore, the study delves into the policy measures implemented in Georgia to combat unemployment and nális sustainable economic development. It scrutinizes the effectiveness of these policies, identifying successes and náli requiring improvement. The insights gained from this nálisis not only contribute to a deeper understanding of the dynamics between unemployment and economic development but also provide valuable lessons for policymakers and stakeholders in Georgia and other regions grappling with similar challenges. As nations worldwide seek to navigate the complex terrain of labor market dynamics and economic prosperity, the case of Georgia serves as an instructive example, highlighting the significance of addressing unemployment as a critical component of a nation’s economic growth strategy.